PRINSIP GOOD CORPORATE GOVERNANCE SEBAGAI STRATEGI DALAM PENGELOLAAN BANK SYARIAH DI INDONESIA - Andrew Shandy Utama (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2018)
Islamic banks are banks that carry outtheir business activities based ons hari a principles. At thet ime of theeconomic crisis in 1998, many conventional banks had collaps edwhile Islamic banks were not affected. After thecrisis, Islamic banking experienced significant developments in Indonesia. What is the strategy in the management of Islamic banks in Indonesia basedon Law Number 21 of 2008? The methodused in this study isnormative legal researc husing the statutory approach. The results of this study explain that from 2008 to 2018 there were no Islamic banks that experienced legal problems, while conventional banks existed, namely Century Bank and IFI Bank. Based on Article 34 of Act Number 21 of 2008 it is affirmed that Islamic banks mustimplement good governance that coverstheprinciples of transparency, accountability, accountability, professionalism and fairness in carrying out their business activities. So, thestrategy in managing Islamic banks in Indonesia applies the principles of good corporate governance.